Horizontal Compression Test: A Proposed Method for Indirect Determination of Tensile Strength of Stiff Soils and Soft Rocks - Guan, Fanfan; Li, Yanrong; Gao, Guohong; Zachert, Hauke; Eichhoff, Gerald; Beroya-Eitner, Mary Antonette (Frontiers in Earth Science, 2022)
Tensile strength is an important parameter in many engineering applications. In loess slopes, for instance, it governs the development and propagation of tension cracks that usually ultimately lead to crack–sliding and toppling failures, which are among the most common modes of slope failure in the Loess Plateau of China. Reliable measurement of tensile strength of geomaterial is therefore a necessity. Commonly used methods for tensile strength measurement have important limitations and shortcomings, which become magnified when dealing with soil and soft rock. This study developed a new indirect tensile test, the Horizontal Compression test, for use with these materials. The proposed method not only involves simple sample preparation and test operation, it also addresses the eccentric force and stress concentration problems that are common in conventional tensile tests. To evaluate the method’s validity, its performance was compared with the ISRM-suggested direct tensile test and the closely related Brazilian test. The tensile strength values from the horizontal compression test strongly correlate with those from the direct tension test, and are more stable than those obtained with either of the two conventional tests. Thus, the proposed method can be used and deemed more suitable for tensile strength determination than these conventional test methods.